2021
DOI: 10.3390/educsci11060255
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn about Science Teachers’ Technology Use during the COVID-19 Pandemic?

Abstract: The purpose of this qualitative research was to describe teachers’ experiences in a technology-mediated teaching context during the COVID-19 pandemic. We mainly focused on teachers’ experiences with technology use (change and variety of the use) and their willingness to use technology in teaching. We designed an interview-based study. The participants were Estonian science teachers who voluntarily agreed to share their experiences about teaching in new and—for most of them—unexpected, distanced learning condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…In concordance with Adov and Mäeots (2021), the current study found that other problems pointed out by the respondents were related to logistics and technical matters. Both external and internal obstacles were reported by the respondents.…”
Section: The Main Hurdles Encountered In Online Teaching During the Covid-19 Pandemicsupporting
confidence: 85%
See 1 more Smart Citation
“…In concordance with Adov and Mäeots (2021), the current study found that other problems pointed out by the respondents were related to logistics and technical matters. Both external and internal obstacles were reported by the respondents.…”
Section: The Main Hurdles Encountered In Online Teaching During the Covid-19 Pandemicsupporting
confidence: 85%
“…These hurdles were found to negatively affect teachers' attitudes toward the e-teaching experience during the pandemic. Adov and Mäeots (2021), for instance, indicated that different internal and external obstacles hinder teachers' use of e-Learning platforms. They observed that poor infrastructure, lack of control, and lack of digital skills are the main obstacles faced by teachers.…”
Section: Teachers' Attitudes Towards Online Educationmentioning
confidence: 99%
“…Teachers played a more crucial role in monitoring students' learning effects, and their psychological or technical problems appeared in online teaching platforms. Recent studies (e.g., Almazova et al, Daumiller et al, Sales et al, Adov & Maeots) showed that teachers needed to positively influence their students who had problems with self-regulated learning ability, attention, and computer literacy [60,76,84,85]. Furthermore, students were inclined to fall into depression or frustration when they met difficulties with distant learning.…”
Section: Online Learning Guardian Of Emotionsmentioning
confidence: 99%
“…Adaptation processes during the pandemic have involved many organizational challenges. Several studies so far have highlighted educational challenges related to the pandemic [4][5][6]. Research has highlighted challenges such as the weakness of online teaching infrastructure, the limited exposure of teachers to online teaching, the information gap, a non-conducive environment for learning at home, and inequality in many countries.…”
Section: Introductionmentioning
confidence: 99%